EXPERIENCE OF 424 ROBOT-ASSISTED OPERATIONS IN ST-PETERSBURG: RADICAL PROSTATECTOMY, PARTIAL AND RADICAL NEPHRECTOMY - S. Kh. Al’-Shukri; M. S. Mosoyan; D. Yu. Semenov; D. M. Il’In (Вестник хирургии имени И.И. Грекова, 2016)
The article presents the results of 257 robot-assisted radical prostatectomies, 135 partial nephrectomies and 32 radical nephrectomies at the period from 2010 to 2016. The operations were performed on robotic complex da Vinci S. The mean operative time was 170±50 min, 158,4±72,2 min and 143,3±67,3 min, the mean blood loss was 130±35 ml, 213,0±102,2 ml and 141,4±49,0 ml for robotic radical prostatectomy, partial and radical nephrectomy, respectively. The mean time of warm ischemia consisted of 13,1±2,7 min. Five-year cancer-specific survival rate was 100%, 100% and 98%. The overall survival rate was 97,5%, 87% and 92% for robotic radical prostatectomy, partial and radical nephrectomy, respectively.